SaO2 as a predictor of exercise-induced hypoxemia in chronic obstructive pulmonary disease at moderate altitude (2019)
Background: Given the high prevalence of chronic obstructive pulmonary disease (COPD) in Bogota (2630 m above the sea), screening methods are required for COPD patients who develop exercise-induced hypoxemia (EIH). Objective: The objective was to measure the productive capacity of basal oxygen saturation for the detection of EIH during the 6-min walking test (6MWT) in patients diagnosed with COPD in a hospital in Bogotá. Design: This was a cross-sectional, retrospective study. Population: Patients diagnosed with COPD with SaO2≥88% who attended the Pneumology Section of the FSFB for a 6MWT between 2013 and 2017 were included in the study. Measurements: Age, sex, anthropometric data, SaO2, SaO2 during 6MWT, and spirometry were evaluated. Results: Ninety-two patients with EIH and 32 patients without EIH were studied. Statistically significant differences were found in SaO2, minimum SaO2 during 6MWT, and BMI (90.8% vs 93%, 80.3% vs 88.9%, and 26.7 kg/m2 vs 23.8 kg/m2, respectively). FEV1 was without statistically significant differences (74.1% vs 78.6%). The ROC curve showed a better cut-off point for detecting EIH with basal SaO2≤92% (sensitivity 76.1%, specificity 62.5%, NPV 47.6%, and PPV 85.4%) and SaO2≤94% as the best sensitivity point (sensitivity 94.6%, specificity 15.6%, NPV 76.3%, and PPV 50%). Conclusion: SaO2 is not a good screening test for EIH in COPD patients at moderate altitude.